Thioredoxin-like protein 2b facilitates colon cancer cell proliferation and inhibits apoptosis via NF-κB pathway. Issue 2 (28th July 2015) - Lu, Yuanyuan; Zhao, Xiaodi; Luo, Guanhong; Shen, Gaofei; Li, Kai; Ren, Gui; Pan, Yan; Wang, Xin; Fan, Daiming
Highlights: Txl-2 is overexpressed in colon cancer tissues and is correlated with tumor staging. Txl-2b promotes cancer cell proliferation, accelerates cell cycle and confers to resistance to apoptosis in a Trx-domain dependent manner. The mechanism by which Txl-2b contributes to cell cycle and apoptosis disruption is possibly dependent on the NF-κB pathway. Txl-2b offers a target for the development of drugs to treat and prevent colon cancer. Abstract: Our previous work identified thioredoxin-like protein 2 (Txl-2), a novel thioredoxin family member, as the target of the monoclonal antibody MC3 which can detect colon cancer with high sensitivity and specificity. In the present study, the function of the most abundant isoform Txl-2b in cell proliferation and apoptosis was investigated. Txl-2 overexpression correlated with increased clinical stages. Inhibition of Txl-2b suppressed cell proliferation, induced cell cycle arrest at the G1/S phase, and led to responsiveness to the vincristine-induced apoptosis in SW620 cells. Txl-2b overexpression in LoVo cells had the opposite effect, which was dependent on Trx domain function. In vivo studies validated that Txl-2b expression promoted colon cancer tumorigenesis in nude mice. Further studies revealed that nuclear factor-κB (NF-κB) signaling was activated by Txl-2b. Inhibition of NF-κB activation partly abrogated the pro-proliferation and anti-apoptotic phenotypes mediated by Txl-2b via reduced Cyclin D1, Bcl-2, Bcl-xL and Survivin expression and increased Caspase-3 activation. Overall, our results indicate that Txl-2b expression stimulates cancer cell proliferation, accelerates the cell cycle and contributes to apoptosis resistance in colon cancer and provides a potential therapeutic target for colon cancer treatment.